Data for "Quantifying behavior and life history events of an Arctic ungulate from year-long continuous accelerometer data" - Schmidt, Niels Martin (Zenodo, 2021)
Data file for the paper "Quantifying behavior and life history events of an Arctic ungulate from year-long continuous accelerometer data" in Ecosphere. The data filerepresents the dataset collected with accelerometer tags on one female muskoxen in northeast Greenland and associated covariates: date and time (TimeUTC), Overall Dynamic Body Acceleration (ODBA) and Pitch as calculated from accelerometer data and mean daily snow depth (snod_sma). Data here are given as included in the models (for a description of data handling and modelling procedures, see article). For further queries please contact nms@bios.au.dk.